A non‐erythropoietic peptide derivative of erythropoietin decreases susceptibility to diet‐induced insulin resistance in mice. (24th November 2014) - Collino, M; Benetti, E; Rogazzo, M; Chiazza, F; Mastrocola, R; Nigro, D; Cutrin, J C; Aragno, M; Fantozzi, R; Minetto, M A; Thiemermann, C
<x xml:space="preserve">Abstract</x> Background and Purpose The haematopoietic activity of erythropoietin (EPO) is mediated by the classic EPO receptor (EpoR) homodimer, whereas tissue‐protective effects are mediated by a heterocomplex between EpoR and the β‐common receptor (βcR). Here, we investigated the effects of a novel, selective ligand of this heterocomplex – pyroglutamate helix B surface peptide (pHBSP) – in mice fed a diet enriched in sugars and saturated fats. Experimental Approach Male C57BL/6J mice were fed a high‐fat high‐sucrose diet (HFHS) for 22 weeks. pHBSP (30 μg·kg−1 s.c.) was administered for the last 11 weeks. Biochemical assays, histopathological and immunohistochemical examinations and Western blotting were performed on serum and target organs (liver, kidney and skeletal muscle). Key Results Mice fed with HFHS diet exhibited insulin resistance, hyperlipidaemia, hepatic lipid accumulation and kidney dysfunction. In gastrocnemius muscle, HFHS impaired the insulin signalling pathway and reduced membrane translocation of glucose transporter type 4 and glycogen content. Treatment with pHBSP ameliorated renal function, reduced hepatic lipid deposition, and normalized serum glucose and lipid profiles. These effects were associated with an improvement in insulin sensitivity and glucose uptake in skeletal muscle. Diet‐induced overproduction of the myokines IL‐6 and fibroblast growth factor‐21 were attenuated by pHBSP and, most importantly, pHBSP markedly enhanced mitochondrial biogenesis in skeletal muscle. Conclusions and Implications Chronic treatment of mice with an EPO derivative, devoid of haematopoietic effects, improved metabolic abnormalities induced by a high‐fat high‐sucrose diet, by affecting several levels of the insulin signalling and inflammatory cascades within skeletal muscle, while enhancing mitochondrial biogenesis.